Partnership for Sustainable Coffee Certification: Linking Up Smallholder Farmers to Global Coffee Market - Arifin, Bustanul; Reed, Michael; Rosanti, Novi; Ismono, Hanung; Budiyuwono, Slamet (The Indonesian Forestry Certification Cooperation, 2022)
This study examines the impacts of partnerships for sustainability certifications in coffee value chains on farm income in Lampung Province, Sumatra-Indonesia. We conducted farm-household surveys, interviewing 171 samples in West Lampung and Tanggamus Districts, consisting of 98 farmers joining partnership and 73 farmers not joining. A probit model is used to determine decisions to join the partnership; ordinary least square (OLS) is used to analyze the determinants of farm income; and Heckman selection-correction model is used to reduce the selection bias in partnership participation. We find some selection in partnerships for sustainability certifications, driven by the age and education of household head, land holding size of coffee farm and the proximity to rural cooperatives-KUBE. The partnership farmers earn higher farm income than those not joining, due to a higher proportion of productive family members. After employing the treatment-effect model, we find that the partnership for sustainability certifications raises farm income, mostly due to higher coffee yield and farm-gate prices. These results reveal the need for policies to support the establishment and encouragement of partnerships for sustainability certifications. The internal control system (ICS) initiated by coffee corporations in implementing the sustainability certifications have improved the trust level between smallholders and global corporations.